A Market Model of Peninsular Malaysian Sawntimber Industry - Shamsudin, Mad Nasir; Othman, Mohd Shahwahid (Universiti Putra Malaysia Press, 1995)
A market model of sawn timber consisting of supply, export demand and domestic demano equations, and excess supply and price as identities was developed. The model can be used to analyse the effect of changes in exogenous variables such as export duty, substitute product prices, forest opening and economic growth on the supply, demand and price of sawn timber.